Etnobotany of Gardens Fruit Plants Minangkabau Community in Payakumbuh Subdistrict, West Sumatera - Aziz, Fadhila; Lestari, Ria Windi; Fitriah, Umi Novita; Manik, Visi Tinta (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Ethnobotany is the study of the relationship between human culture and plants. Ethnobotany plays important role in understanding the behavior of the people of an area in utilizing the plants around them. This study aims to determine the utilization of garden fruit plants by Minangkabau community in Payakumbuh subdistrict, West Sumatra. The method used in this study was purposive random sampling. The data were collected by conducted by direct observation and interview. The data were analyzed descriptively with a quantitative approach using the Index of Culture Significance (ICS). The results showed that the Payakumbuh sub-district home garden category was classified as moderate, are planted with 34 species of fruit plants from 19 genera. Fruit plants that are often found in the home garden of the Payakumbuh subdistrict are bananas (Musa sp.) around 51.02% and papaya (Carica papaya) around 13.80%. Fruit plants that are cultivated besides being consumed in the form of fruit are also used as medicine, shade plants, seasonings, cultural rituals, and food wrappers. Parts of the plant that are utilized besides fruits are leaves, canopy, fruit skin, flowers, and seeds. Banana (Musa sp.) has the highest ICS value.